The impact of multiple interviews on the accuracy and narrative coherence of children's memories. Issue 10 (26th November 2022) - Szojka, Zsofia A.; Nicol, Annabelle; Frenguelli, Non Davis; Rooy, David La; Henderson, Hayden
ABSTRACT: This study investigated the accuracy and narrative coherence of children's accounts of a staged event across two interviews in comparison to a control condition to discern between the effects of repeated recall and delay between interviews. Seventy-six 8–11-year-olds took part in a first aid training session. Half of the children were randomly assigned to be interviewed using open-ended questions twice, one week after the event and five weeks after the event, whilst the other half were interviewed only once, five weeks after the event. Supporting the hypotheses, children reported more details over the course of two interviews than in a single interview either 1-week or 5-weeks after the event, and details that remained consistent across the two interviews were more accurate than reminisced details. The increased completeness of children's accounts in two interviews was accompanied by an increase in the use of markers of causal-temporal connectedness. The hypothesis regarding the negative effect of delay on the accuracy of children's testimony was partially supported, as details reported in the first, 1-week interview were more accurate than details in the single 5-week interview. Results demonstrate that multiple interviews can increase the narrative coherence of children's testimony without decreasing their accuracy.